1998
DOI: 10.1089/cbr.1998.13.395
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proliferation and DNA Synthesis of a Human Tumor Cell Line (HELA) Caused by Short Treatment with the Antianemic Drug Jectofer (Ferric-Sorbitol-Citrate) and the Lipid Peroxidation Product 4-Hydroxynonenal

Abstract: Anti-anaemic drug, ferric-sorbitol-citrate complex (FSC), inhibit tumour cell growth through the mechanisms which are complex and not entirely understood. The probable mechanisms of described effects of iron is iron-induced oxidative stress of the treated cells. Hence, the effects of FSC on HeLa cell growth in vitro were compared with the biological activity of one of the major mediators of the oxygen free radicals--aldehyde 4-hydroxinonenal (HNE), to see if the effects of FSC and of HNE resemble each other. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The resulting functional modifications of key cellular proteins have been well documented [64,67,68]. Particularly striking among the many physiological effects of 4‐HNE is the modulation of the cell cycle [69–71], differentiation [72–74], and apoptosis [73,75,76]. It is intriguing to speculate that 4‐HNE may act as a signal during embryogenesis and tissue remodeling when the above processes are prominent.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting functional modifications of key cellular proteins have been well documented [64,67,68]. Particularly striking among the many physiological effects of 4‐HNE is the modulation of the cell cycle [69–71], differentiation [72–74], and apoptosis [73,75,76]. It is intriguing to speculate that 4‐HNE may act as a signal during embryogenesis and tissue remodeling when the above processes are prominent.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 As we have previously shown, iron in the form of ferric-sorbitol-citrate (FCS) (Jectofer; Astra, Linz, Austria) inhibited the proliferation of CaCo2 (colon carcinoma), Hep2 (laryngeal carcinoma), MiaPaCa2 (pancreatic carcinoma), and HeLa (cervix carcinoma) cell lines but did not affect the proliferation of the nonmalignant fibroblast cell line HEF522 and human bone marrow cells. 7,8 FSC also caused a regression of B16 mouse melanoma in vitro and in vivo. 9 An increased number of cells in G1 and in early Sphase suggested that iron excess blocked the cell cycle before the onset of DNA synthesis.…”
Section: Introductionmentioning
confidence: 86%
“…Final concentrations of the FSC iron were from 10 Ϫ5 to 10 Ϫ3 M. These concentration ranges were chosen on the basis of previous experience with the ability of FSC iron to modify tumor cell growth in vitro. 7,8…”
Section: Ferric-sorbitol-citrate Complexmentioning
confidence: 99%
See 1 more Smart Citation